Motivations to perform care practices in high-risk pregnancy (Research, Society and Development, 2021)
Objective: to know the care practices performed by high-risk pregnant women to preserve pregnancy and the motivations to perform them. Method: qualitative research conducted with ten women who experienced high-risk pregnancy. The data were produced through semi-structured interviews and submitted to thematic content analysis. The research followed the ethical aspects, according to the norms of resolution number 466/12, being approved by opinion 222.320. Results: the motivations for the care practices performed by the pregnant women aimed to ensure the baby's health and encompassed care with food, rest and the removal of stressful factors. They were practices departing from informal and professional knowledge. Conclusion: high-risk pregnant women performed care that involved demands from different spheres of needs and demonstrated the need for emotional support due to changes in their routine and lifestyle.